2023
DOI: 10.1111/1460-6984.12909
|View full text |Cite
|
Sign up to set email alerts
|

Affective prosody disorders in adults with neurological conditions: A scoping review

Abstract: BackgroundIndividuals with affective‐prosodic deficits have difficulty understanding or expressing emotions and attitudes through prosody. Affective prosody disorders can occur in multiple neurological conditions, but the limited knowledge about the clinical groups prone to deficits complicates their identification in clinical settings. Additionally, the nature of the disturbance underlying affective prosody disorder observed in different neurological conditions remains poorly understood.AimsTo bridge these kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“… 10 , 11 For AD patients, although it is less prominent, studies have reported their difficulty in recognizing emotional expressions across different types of emotions, where it was most pronounced in recognizing “fear” and the least for “surprised.” 12 For DLB, a few studies have suggested deficits in recognizing emotional expressions depending on the type of emotion, for example, diminished recognition of “surprised” faces 13 note that investigations into emotional processing alterations in DLB are still limited. 14 Moreover, studies on the neural correlates of impaired emotional recognition have also suggested disease‐specific patterns. 10 For example, in AD, deficits in emotion recognition were associated with brain regions such as the anterior cingulate, 15 , 16 while in DLB, they were associated with regions including the middle frontal gyrus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 11 For AD patients, although it is less prominent, studies have reported their difficulty in recognizing emotional expressions across different types of emotions, where it was most pronounced in recognizing “fear” and the least for “surprised.” 12 For DLB, a few studies have suggested deficits in recognizing emotional expressions depending on the type of emotion, for example, diminished recognition of “surprised” faces 13 note that investigations into emotional processing alterations in DLB are still limited. 14 Moreover, studies on the neural correlates of impaired emotional recognition have also suggested disease‐specific patterns. 10 For example, in AD, deficits in emotion recognition were associated with brain regions such as the anterior cingulate, 15 , 16 while in DLB, they were associated with regions including the middle frontal gyrus.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to emotional recognition, emotional expression in dementia patients, which is also crucial for social interactions, 9 , 14 , 17 affecting individuals' mental health and quality of life, 9 remains largely uninvestigated. To the best of our knowledge, no study has explored alterations in emotional expressions in DLB or compared with those in AD.…”
Section: Introductionmentioning
confidence: 99%